An evaluation of Cost Performance of Public Projects in the Free State Province of South Africa - Monyane, T.G; Okumbe, J.O (Bloemfontein : Central University of Technology, Free State, 2012)
The primary objective of this study is to identify major cuases of construction cost overruns in the Free State Province of South Africa in order to propose effective control measures. The study is based on a review of related literature and a subsequent field work. The survey investigated the factors that have significant effects on cost overruns, especially in the public sector, during the three major phases of a construction project life cycle. Results indicate that the most severe cost overruns causes are inadequate project planning, delays in issuing information to contractors and poor workmanship in term of quality. And the best remedial measures were adequate pre-contract planning, proper implementation, timely resolution of disputes and being quality focus. The level of performance revealed 60% of the projects deviated from the agreed project costs. Practical implication of the findings is that stakeholders need to carefully take into account the factors that influence cost overruns in each stage of the life cycle of the projects that they undertake in the province.
Published Article
Keywords: Construction; Cost; Performance; Free State; South Africa